Rastreamento da doença renal crônica em idosos cuidadores cadastrados na atenção primária à saúde - Bento, Sirlei Ricarte (Universidade Federal de São Carlos, 2020)
Currently, there is a progressive increase in the number of elderly people providing care to another elderly person. The task of caring can harm the health of the caregiver. Elderly caregivers are more prone to comorbidities that, in most cases, are identified as risk factors for chronic kidney disease (CKD). Thus, this dissertation aims to assess the risk for CKD and to identify the factors associated with CKD in elderly caregivers of elderly in primary health care. And to answer this objective, this work is organized in the form of articles. The first article presents an integrative review of the literature on the methods of screening CKD in the population. A search for studies was conducted in the period 2014-2018, in English, Portuguese and Spanish in the following databases: SCIELO, LILACS, PubMed and SCOPUS, using the following combination of descriptors: "screening" AND "renal insufficiency chronic ". For the selection of the articles, the Preferred Reporting Items for Systematic Review and Meta-Analysis method was used. As a result, most of them used the measurement of serum creatinine and glomerular filtration rate. Among the screening instruments, three studies used Screening for Occult Renal Disease, which can contribute to the development of accessible and low-cost strategies for screening CKD in the population. The second article presents the results of the risk of CKD and the associated factors. A transversal study with elderly (n = 111) familiar caregivers of elderly with whom they lived was conducted, and for such, the instruments for data collection were characterization questionnaires of sociodemographic, clinical, care and screening for hidden kidney disease for evaluation of the risk of chronic kidney disease. All ethical precautions were observed. Descriptive statistics were performed and for the SCORED instrument, analyzes were performed with and without the age item for CKD screening. For the associated factors, a multiple logistic regression analysis was performed using the stepwise forward method. The risk of CKD was 99.1% and after excluding the age variable from the questionnaire, a risk of 15.3% was observed. The number of medications was the factor associated with the risk of chronic kidney disease (OR = 1.257). In conclusion, the risk of CKD in elderly caregivers for the elderly is high and the use of medication is associated with this risk. It is vital that health professionals are trained to implement strategies to prevent future health problems for elderly caregivers with early identification of the risk for CKD, avoiding the burden on the health system.
Screening for chronic kidney disease in elderly caregivers registered in primary health care
Keywords: Idoso; Cuidador; Insuficiência renal crônica; Enfermagem; Elderly; Caregiver; Chronic kidney failure; Nursing; CIENCIAS DA SAUDE::ENFERMAGEM